P.064 Physician Approaches to Imaging and Revascularization for Acutely Symptomatic Carotid Stenosis: Insights from the Hot Carotid Qualitative Study. (November 2021) - Ganesh, A; Beland, B; Jewett, G; Campbell, DJ; Varma, M; Singh, R; Al-Sultan, A; Wong, J; Menon, BK
Abstract : Background: Evidence informing the choice between endarterectomy and stenting for acutely symptomatic carotid stenosis ("hot carotid") is dated, and uncertainties remain regarding the optimal imaging modality. We sought to explore the thoughts of stroke physicians regarding the perioperative management of patients with acute symptomatic carotid stenosis. Methods: We conducted semi-structured interviews regarding "hot carotid" management with purposive sampling of 20 stroke physicians from 14 centres in North America, Europe, Asia, and Australia. We identified key themes using conventional qualitative content analysis. Results: Timely imaging availability, breadth of information gained, and surgeon/interventionalist preference emerged as important themes informing the choice of imaging modality. Multidisciplinary decision making, operating room/angiography suite availability, and implications of patient age and infarct size were important themes related to the choice of revascularization. Areas of uncertainty included utility of carotid plaque imaging, timing of revascularization, and the role of intervention with borderline stenosis or intraluminal thrombus. Conclusions: Our qualitative analysis revealed themes that were important to stroke experts. Teams designing international trials will have to accommodate identified variations in practice patterns and take into consideration areas of uncertainty, such as timing of revascularization, imaging of carotid plaque and non-stenotic features of carotid disease (intraluminal thrombus, plaque morphology).